Optimizing Vane Number for Enhanced Performance of Mist Blower Nozzle in Agricultural Spraying - Pramuhadi, Gatot; Walpuri, Chitra Gusti Indah; Sidik, Ahmad Jaelani; Agusta, Waqif (The University of Lampung, 2024)
The objective of this study is to optimize the number of vanes equipped in the propeller of a mist blower's nozzle. Performance tests were conducted on the approved sprayer test bed, also known as a patternator, to measure several parameters, including effective spraying discharge, effective spraying width, spraying angle, effective spraying height, effective spraying range, droplet diameter, and droplet density. The vane number was optimized using the weighting method. The results indicate that increasing the number of vanes used is directly correlated with higher values of effective spraying width (ESW), spraying angle, effective spraying range (ESR), and droplet density. Conversely, it is inversely correlated with the value of effective spraying discharge (ESD), effective spraying height (ESH), and droplet diameter. The vane number was optimized using the weighting method. The most effective results in the mist blower performance test are achieved by using 12 vanes. This configuration produces droplets with a diameter of 195.44 ±9.68 μm and a density of 320 ± 17.44 droplets/cm2. The mist blower also has ESW of 136 ± 1.73 cm, ESH of 68.14 ± 4.19 cm, ESD of 4.41 ± 0.14 L/min, and ESR of 5.76 ± 0.04 m. Keywords: Agricultural spraying, Mist blower, Nozzle optimization, Performance evaluation, Vane number.